CSRD and Data – How companies collect and analyze data to track sustainability metrics - Fruhwald, Jakob (My University, 2024)
This master thesis seeks to answer the question how companies can best collect the necessary data required for the newly CSRD report and analyze the data collected for sustainability initiatives. Semi-structured interviews were conducted with ten participants of six companies. The findings of the interviews were analyzed through the grounded theory approach by Gioia, with three derived agglomerations. My analysis shows that while there are multiple possible use cases, structured data analysis isn’t introduced yet, and most companies are still struggling with how to properly collect and report the data. Additionally, the study finds multiple issues with the Corporate Sustainability Reporting Directives itself, such as an unclear taxonomy. I conclude that while there isn’t a clear way of how companies use it, conducting organized sustainability reporting and deriving appropriate sustainability initiatives will increase in importance for the companies. Companies should recognize that investing in sustainability will most likely pay off in the long term. For a study of this kind, the sample size is rather on the small side, which is important for readers to keep in mind.
Keywords: CSRD, Sustainability, Sustainability Reporting, Data Analysis, Green IS/IT